Financial technology and its impact on digital literacy in India: Using poverty as a moderating variable - Rahul Singh Gautam; Shailesh Rastogi; Aashi Rawal; Venkata Mrudula Bhimavarapu; Jagjeevan Kanoujiya; Samaksh Rastogi (Journal of Risk and Financial Management, 2022)
Financial technology is a powerful tool in financial infrastructure, used to strengthen and smooth the delivery of financial services into the broader space. Financial technology involves software, applications, and other technologies designed to improve and automate traditional forms of financial services for businesses established in different areas. The authors aimed to explore the impact of financial technology on the digital literacy rate in India, by utilizing the poverty score as a moderating variable. The panel data analysis (PDA) has been employed in the current study. Data from 29 states and two union territories (UTs) of India were considered for three financial years, i.e., 2017-2018 to 2019-2020. The study's findings reveal that Kisan Credit Cards (KCCs), both in terms of numbers and amount, are positively associated with the literacy rate. However, ATMs are negatively significant in association with literacy rate. Furthermore, the study's empirical results show that KCCs and ATMs positively impact literacy when interacting with poverty scores. The study's findings bring noteworthy implications for the government and other officials to understand the situation at the ground level of Indian states and UTs while forming new rules and policies for society's betterment, particularly in finance and digital literacy. Additionally, the findings imply that ordinary people living in urban and rural areas of India should take advantage of financial technology and get motivated towards digital literacy.
Keywords: 650; ATMs; digital literacy; financial technology; Kisan credit cards